(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2017)
درسنا في هذا البحث مسألة التتميم في منطق الجبر ثلاثي القيمة على منطق لوكاسفيتش ثلاثي القيمة بالنسبة لجملة أدوات منطقية تامة حيث تمت دراسة هذه المسألة في منظومة اشتقاق غاسبرغ وتقديم دراسة شاملة تضمنت أهم النظريات و قواعد الاشتقاق التي تم وضعها والتي أدت إلى تقديم برهان مميز لنظرية التتميم في منطق لوكاسفيتش ثلاثي القيمة. We study in this research completeness problem in three valued algebraic logic on Lukasiewicz 3 valued logic for a functionally complete set of connectives where we studied this problem in Wajseberg derivation system and we presented a comprehensive study of the most important theorems and derivation rules which led to a very unique and special proof of completeness theorem in Lukasiewicz 3 valued logic.